The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13014-020-01607-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and dosimetry analysis of CT-guided 125I seed implantation assisted with 3D-printing non-co-planar template in locally recurrent rectal cancer

Abstract: Background: Locally recurrent rectal cancer (LRRC) after surgery or external beam radiotherapy (EBRT) is a serious challenge for which no standard treatment is defined. In the present study, we investigated the feasibility of computed tomography (CT)-guided radioactive 125 I seed (RIS) implantation assisted with three-dimensional printing non-coplanar template (3D-PNCT) in LRRC patients who previously received surgery or EBRT. Methods: Sixty-six patients with LRRC treated by CT-guided RIS implantation in our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Wang et al . [ 17 ] studied 66 patients with LRRC who were previously treated with EBRT or surgery. Median overall survival (OS) and local control (LC) time were 14.7 and 12.2 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al . [ 17 ] studied 66 patients with LRRC who were previously treated with EBRT or surgery. Median overall survival (OS) and local control (LC) time were 14.7 and 12.2 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on prostate cancer suggested that the prognosis of patients with D 90 > 140 Gy and V 100 > 90% was significantly better compared to patients with D 90 < 140 Gy or D 100 < 90% [ 19 , 20 , 21 ]. A study on LRRC revealed that patients with D 90 > 130 Gy or V 100 > 90% had a superior prognosis [ 17 ]. One-year local control rates for patients with D 90 > 130 Gy and V 100 > 90% were 72.4% and 69.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT)-guided iodine-125 seed implantation ( 125 I-SI) is proved to be safe and effective when applied in head and neck, thoracic, abdomen, retroperitoneal, and vertebral cancers, especially for locally advanced or recurrent solid cancers after EBRT [6][7][8][9][10][11][12]. 125 I-SI may be applied as a salvage therapy for rCWC alone or as a boost to EBRT, due to rapid dose falling-off and sparing of surrounding organs, while the chest wall is irregular and it may be difficult to perform CT-guided 125 I-SI in patients with rCWC.…”
Section: Purposementioning
confidence: 99%
“…3D-printing non-co-planar template (3D-PNCT) is helpful for high quality performance of CT-guided 125 I-SI [7,8,[12][13][14]. The safety, accuracy, and feasibility of 3D-PNCT application in CT-guided 125 I-SI for cancers raised in complex locations, such as the head and neck, has been explored and reported [7,8,10,[12][13][14][15]. However, the literature on the accuracy and dosimetric analysis of 3D-PNCT-assisted 125 I-SI for rCWC is scarce.…”
Section: Purposementioning
confidence: 99%
“…A low-dose-rate (LDR) with the computer tomography (CT) guidance and 3-dimensional (3D)-printing non-coplanar template (PNCT) assistance, RISI can achieve an accurate dose delivery and spare the normal tissues. Up to now, 3D PNCT-assisted RISI has presented promising results in the salvage treatment of several kinds of recurrent tumors [ 15 , 16 , 17 , 18 ] and has been referenced in the National Comprehensive Cancer Network guidelines for the management of a locally recurrent rectal cancer [ 19 ]. Meanwhile, existing studies have preliminarily confirmed the efficacy and safety of RISI in the treatment of cervical cancer [ 16 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%